Evans, The Forging Of The Modern State - Early Industrial Britian, Emsley, Crime And Society In England, 1750-1900 - Blackey, Robert (Teaching History: A Journal of Methods, 1997)
New editions often suggest that a book has justified a publisher's investment; they also provide authors an opportunity both to correct inevitable errors and to bring their efforts up to date. Here are two worthwhile and sophisticated books, each intended for classroom use, that have been given editorial second wind. Evans's textbook takes into account recent research, with special attention to the Industrial Revolution and its consequences (i.e., about social change and whether there actually was an Industrial Revolution in late eighteenth and early nineteenth-century Britain).